In the shadow of the Holocaust Poland, the United Nations War Crimes Commission, and the search for justice - Fleming, Michael 1974- (Cambridge University Press, 2022)
In the midst of the Second World War, the Allies acknowledged Germany's ongoing programme of extermination. In the Shadow of the Holocaust examines the struggle to attain post-war justice and prosecution. Focusing on Poland's engagement with the United Nations War Crimes Commission, it analyses the different ways that the Polish Government in Exile (based in London from 1940) agitated for an Allied response to German atrocities. Michael Fleming shows that jurists associated with the Government in Exile made significant contributions to legal debates on war crimes and, along with others, paid attention to German crimes against Jews. By exploring the relationship between the UNWCC and the Polish War Crimes Office under the authority of the Polish Government in Exile and later, from the summer of 1945, the Polish Government in Warsaw, Fleming provides a new lens through which to examine the early stages of the Cold War
Title from publisher's bibliographic system (viewed on 23 Dec 2021)
Keywords: United Nations War Crimes Commission; Vereinte Nationen -- War Crimes Commission; Geschichte 1940-1948; World War, 1939-1945 / Poland; World War, 1939-1945 / Governments in exile; Holocaust, Jewish (1939-1945) / Poland; World War, 1939-1945 / Atrocities / Germany; War crimes investigation; Judenvernichtung; Exilregierung; Kriegsverbrechen; Zweiter Weltkrieg; Poland / Politics and government / 1918-1945; Polen